Chemical Cross-Linking Enables Drafting ClpXP Proximity Maps and Taking Snapshots of In Situ Interaction Networks. Issue 1 (17th January 2019) - Fux, Anja; Korotkov, Vadim S.; Schneider, Markus; Antes, Iris; Sieber, Stephan A.
Summary: Detection of dynamic protein-protein interactions within complexes and networks remains a challenging task. Here, we show by the example of the proteolytic ClpXP complex the utility of combined chemical cross-linking and mass spectrometry (XL-MS) to map interactions within ClpP and ClpX as well as across the enigmatic ClpX hexamer-ClpP heptamer interface. A few hot-spot lysines located in signature loops in ClpX were shown to be in proximity to several structural regions of ClpP providing an initial draft of the ClpX-ClpP interaction. Application of XL-MS further confirmed that Listeria monocytogenes ClpX interacts with the heterooligomeric ClpP1/2 complex solely via the ClpP2 apical site. Moreover, cellular interaction networks of human and bacterial proteases were elucidated via in situ chemical cross-linking followed by an antibody-based pull-down against ClpP. A subsequent mass spectrometric analysis demonstrated an up to 3-fold higher coverage compared with co-immunoprecipitation without cross-linker revealing unprecedented insight into intracellular ClpXP networks. Graphical Abstract: Highlights: Mapping of ClpP-ClpX interfaces by cross-linking and mass spectrometry Listeria ClpX interacts solely with ClpP2 of the heterooligomeric ClpP1/2 complex Cross-linking/co-immunoprecipitation reveals cellular ClpP interaction partners Abstract : Fux et al. applied cross-linking combined with mass spectrometry (XL-MS) to elucidate the interactions between the peptidase ClpP and its chaperone ClpX, revealing several contacts involving flexible loops of ClpX. Further, XL-co-immunoprecipitation was used to study the intracellular interactors of bacterial and human ClpP, revealing insights into molecular networks.